Pandangan Hukum Islam Terhadap Pembatasan Usia Pernikahan : Islamic Law's View on Marriage Age Restrictions - Usman Syiddiq; Sirajuddin, Sirajuddin; Syandri, Syandri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine the views of munākaḥāt fiqh regarding the limitation of marriage age. This research is a library research using a juridical-comparative approach and a psychological approach. The results of the research achieved in this study are: In Islamic law there is no minimum age limit for marriage, as long as the marriage does not have a negative impact on the bride and groom, this also applies to children who are still under the age of marriage. However, it would be nice if the marriage was prepared carefully in advance, especially preparing psychological, physical and spiritual readiness. Setting a minimum age limit in marriage is not against Islamic law, as long as the goal is to reject harm and/or bring benefits to society.